2012
DOI: 10.3389/fphar.2012.00050
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channels as Targets for Volatile Anesthetics

Abstract: The molecular mechanisms of modern inhaled anesthetics are still poorly understood although they are widely used in clinical settings. Considerable evidence supports effects on membrane proteins including ligand- and voltage-gated ion channels of excitable cells. Na+ channels are crucial to action potential initiation and propagation, and represent potential targets for volatile anesthetic effects on central nervous system depression. Inhibition of presynaptic Na+ channels leads to reduced neurotransmitter rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 66 publications
0
59
0
1
Order By: Relevance
“…Potential synaptic volatile anesthetic targets involved in regulating transmitter release include glutamate receptors, Na v channels (44), K 2P channels (45), nicotinic acetylcholine receptors (34), Ca v channels (46), neurotransmitter transporters (47,48), and SNARE proteins (8,49). Evidence suggests that the presynaptic effects of volatile anesthetics on neurotransmitter release are mediated by reduced nerve terminal excitability from inhibition of Na v channels rather than direct inhibition of Ca 2+ influx by inhibition of Ca v channels (7,44,50,51). A critical distinction is between presynaptic reductions in Ca 2+ influx involving direct inhibition of Ca v (e.g., 52) or indirect effects involving alterations in the presynaptic AP waveform as a result of effects on other ion channels including K v and Na v (35,50,51,53).…”
Section: Discussionmentioning
confidence: 99%
“…Potential synaptic volatile anesthetic targets involved in regulating transmitter release include glutamate receptors, Na v channels (44), K 2P channels (45), nicotinic acetylcholine receptors (34), Ca v channels (46), neurotransmitter transporters (47,48), and SNARE proteins (8,49). Evidence suggests that the presynaptic effects of volatile anesthetics on neurotransmitter release are mediated by reduced nerve terminal excitability from inhibition of Na v channels rather than direct inhibition of Ca 2+ influx by inhibition of Ca v channels (7,44,50,51). A critical distinction is between presynaptic reductions in Ca 2+ influx involving direct inhibition of Ca v (e.g., 52) or indirect effects involving alterations in the presynaptic AP waveform as a result of effects on other ion channels including K v and Na v (35,50,51,53).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any interference with sensory communications, even with a gradual dose-response, can contribute to the overall dynamics of the steep phase transition. In this regard, voltagegated Na + channels (Na V ) are likely to be a relevant molecular target for general anesthetics (6,7). Consistent with enhanced inhibition of fast firing neurons, volatile anesthetics may inhibit neurotransmitter release through action on presynaptic Na V , stabilize the fast-inactivated state of neuronal Na V , and depress Na + current during high-frequency stimulation (8,9).…”
mentioning
confidence: 99%
“…Previous work showed that inhaled general anesthetic agents, including sevoflurane, isoflurane, desflurane, and halothane, mediate inhibition by increasing the rate of Na + channel inactivation, hyperpolarizing steady-state inactivation, and slowing recovery from inactivation (11,(15)(16)(17)(18). Inhibition of presynaptic Na V channels in the spinal cord is proposed to lead to inhibition of neurotransmitter release, facilitating immobilization-one of the endpoints of general anesthesia (14,19,20). Despite the importance of Na V channels as general anesthetic targets, little is known about interaction sites or the mechanisms of action.…”
mentioning
confidence: 99%
“…Many families of ion channels are modulated by general anesthetic agents, including ligand-gated, voltage-gated, and nongated ion channels (2,(5)(6)(7). Mammalian voltage-gated Na + (Na V ) channels, which mediate the upstroke of the action potential, are regulated by numerous inhaled general anesthetic agents (8)(9)(10)(11)(12)(13)(14), which generally cause inhibition. Previous work showed that inhaled general anesthetic agents, including sevoflurane, isoflurane, desflurane, and halothane, mediate inhibition by increasing the rate of Na + channel inactivation, hyperpolarizing steady-state inactivation, and slowing recovery from inactivation (11,(15)(16)(17)(18).…”
mentioning
confidence: 99%